RLC Equivalent Circuit Synthesis Method for Structure-Preserved Reduced-Order Model of Interconnect in VLSI (Communications in Computational Physics, 2018)
This paper aims to explore RLC equivalent circuit synthesis method for reduced-order models of interconnect circuits obtained by Krylov subspace based model order reduction (MOR) methods. To guarantee pure RLC equivalent circuits can be synthesized, both the structures of input and output incidence matrices and the block structure of the circuit matrices should be preserved in the reduced-order models. Block structure preserving MOR methods have been well established. In this paper, we propose an embeddable Input-Output structure Preserving Order Reduction (IOPOR) technique to further preserve the structures of input and output incidence matrices. By combining block structure preserving MOR methods and IOPOR technique, we develop an RLC equivalent circuit synthesis method RLCSYN (RLC SYNthesis). Inline diagonalization and regularization techniques are specifically proposed to enhance the robustness of inductance synthesis. The pure RLC model, high modeling accuracy, passivity guaranteed property and SPICE simulation robustness make RLCSYN more applicable in interconnect analysis, either for digital IC design or mixed signal IC simulation.